(untitled) (American Journal of Islam and Society, 2012)
Although the revolution in Syria is unfolding within the modern political boundaries of this country, its proper understanding is not attainable without putting it in a larger historical context, which includes the adjacent geographical areas of the Levant, Bilad al-Sham. Without such a broader view, the appreciation of the complexity of the Syrian case is not possible, nor accounting for its consequences and anticipating its future. Probably, in no case, is the mess of colonial legacy more visible than it is in Syria. The pathway of this legacy marks the future development of the country, and its implications are facing the revolution today with arduous challenges. The complexity of the Syria case is not limited to the political dimension; it is also complex at the meta-cultural level. Furthermore, the change in Syria has consequences for the region as whole ‒ it will institutionalize the Arab Spring as an unavoidable political force, and it will energize the process of cultural reformation and the recovery of a civilizational Muslim identity ...